2015
DOI: 10.3109/0284186x.2015.1096020
|View full text |Cite
|
Sign up to set email alerts
|

Does long-term survival exist in pancreatic adenocarcinoma?

Abstract: Background:We conducted a population-based study to investigate long-term survival in patients diagnosed with a (suspected) pancreatic adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…A rather large proportion of low stage tumors in this group most likely explains this. Furthermore, among this group, a large proportion concerned a pathologically unverified tumor (76%), what may have led to longer survival due to misclassification [35]. In addition, older patients receiving tumor targeting treatment seem to have similar survival benefit as younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…A rather large proportion of low stage tumors in this group most likely explains this. Furthermore, among this group, a large proportion concerned a pathologically unverified tumor (76%), what may have led to longer survival due to misclassification [35]. In addition, older patients receiving tumor targeting treatment seem to have similar survival benefit as younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, chemotherapy use and survival of elderly NR‐M0 patients may be slightly overestimated in our study, while early mortality may be underestimated. Survival may also be slightly overestimated because some patients of the large group without histological confirmation of pancreatic cancer were incorrectly diagnosed . Despite these limitations, the available unselected data of an often neglected group of pancreatic cancer patients revealed important findings about trends in everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Survival may also be slightly overestimated because some patients of the large group without histological confirmation of pancreatic cancer were incorrectly diagnosed. 24 Despite these limitations, the available unselected data of an often neglected group of pancreatic cancer patients revealed important findings about trends in everyday clinical practice. Secondly, survival trends of NR-M0 patients in the course of the study period must be interpreted with caution as a result of changing characteristics of this subgroup and possible residual 4950 | van der GeeST eT al.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in the United States based on data from Surveillance, Epidemiology, and End Results registry has shown that a pancreatectomy is associated with statistically significant increased survivals for patients with resectable PDAC (i.e., stage I/ II), compared with any other form of therapy (3). Furthermore, a recent study performed in the Netherlands has shown that the percentage of patients with PDAC who survived more than 5 years is significantly higher after resection (10.1%), compared with patients with unresected localized or metastatic disease (0.5% and 0.1%, respectively) (4). Median overall survival time after resection for PDAC is approximately two years (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%